The elite athlete as a special risk traveler and the jet lag's effect: lessons learned from the past and how to be prepared for the next Olympic Games 2020 Tokyo? - Silva, Maria Raquel (2021)
Elite athletes have to travel long-haul distances and cross multiple meridians; thus, a unique syndrome named as jet-lag is induced. Furthermore, traveler athletes are submitted to several factors negatively affecting their well-being and athletic performance. This qualitative descriptive study aims to promote safely and future promising participations of elite athletes in great events, such as the next Olympic Games 2020 Tokyo, based on the chronobiology of jet-lag, factors affecting the traveler athlete and previous experiences from the 2014 FIFA World Cup Brazil, the 2018 FIFA World Cup Russia and the Olympic Games Rio 2016. Methods: A narrative review of the literature across a broad cross-section of the chronobiology of jet-lag and factors affecting the traveler athlete was undertaken. In addition, a general analysis based on the past sport events aforementioned is also included. Results: The jet-lag disorder may occur after transmeridian travel over more than three time-zones and the resynchronization is dependent on the direction and number of the time-zones crossed and the availability and the intensity of local circadian time cues. Also the athlete's ability to sleep, eat, get hydrated and train, are essential, as well as, others individual tolerance differences, such as age, gender, chronotype and ethnic differences. Athletes should arrive a number of days before the competition according to the number of time-zone transitions experienced. Conclusions: Jet-lag is usually benign and self-limited, but can occasionally have serious consequences for the athlete's mental and physical health and performance. A good plan concerning the athlete's traveling schedule, sleeping, eating and training before and after travelling is mandatory.